2022
DOI: 10.1017/s0007114522002197
|View full text |Cite
|
Sign up to set email alerts
|

The impact of increasing the availability of lower energy foods for home delivery and socio-economic position: a randomised control trial examining effects on meal energy intake and later energy intake

Abstract: Increasing the availability of lower energy food options is a promising public health approach. However, it is unclear the extent to which availability interventions may result in consumers later ‘compensating’ for reductions in energy intake caused by selecting lower energy food options, and to what extent these effects may differ based on socioeconomic position (SEP). Our objective was to examine the impact of increasing availability of lower energy meal options on immediate meal energy intake and subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…There are also several limitations to the evidence. The vast majority of studies included in this review used hypothetical choices or assessment of food choice during one meal (for an exception see 14 ). Individuals may feel licensed to overeat after making healthier food choices, leading some to “compensate” for choices by consuming more energy at later meals.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are also several limitations to the evidence. The vast majority of studies included in this review used hypothetical choices or assessment of food choice during one meal (for an exception see 14 ). Individuals may feel licensed to overeat after making healthier food choices, leading some to “compensate” for choices by consuming more energy at later meals.…”
Section: Discussionmentioning
confidence: 99%
“…When studies reported categorizing participants as “higher” and “lower” in SEP, the categorization used in the paper was retained. For example, lower SEP was most often defined as up to A level (US equivalent: Advanced Placement [AP] examinations) and higher SEP as higher education (US equivalent: above high school) (e.g 11,14,17 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations